Light‐distortion analysis as a possible indicator of visual quality after refractive lens exchange with diffractive multifocal intraocular lenses. Issue 3 (March 2015) - Brito, Pedro; Salgado‐Borges, José; Neves, Helena; Gonzalez‐Meijome, José; Monteiro, Manuel
Abstract : Purpose : To study the perception of light distortion after refractive lens exchange (RLE) with diffractive multifocal intraocular lenses (IOLs). Setting : Clínica Oftalmológica das Antas, Porto, Portugal. Design : Retrospective comparative study. Methods : Refractive lens exchange was performed with implantation of an AT Lisa 839M (trifocal) or 909MP (bifocal toric) IOL, the latter if corneal astigmatism was more than 0.75 diopter (D). The postoperative visual and refractive outcomes were evaluated. A prototype light‐distortion analyzer was used to quantify the postoperative light‐distortion indices. A control group of eyes in which a Tecnis ZCB00 1‐piece monofocal IOL was implanted had the same examinations. Results : A trifocal or bifocal toric IOL was implanted in 66 eyes. The control IOL was implanted in 18 eyes. All 3 groups obtained a significant improvement in uncorrected distance visual acuity (UDVA) ( P < .001) and corrected distance visual acuity (CDVA) ( P = .001). The mean uncorrected near visual acuity (UNVA) was 0.123 logMAR with the trifocal IOL and 0.130 logMAR with the bifocal toric IOL. The residual refractive cylinder was less than 1.00 D in 86.7% of cases with the toric IOL. The mean light‐distortion index was significantly higher in the multifocal IOL groups than in the monofocal group ( P < .001), although no correlation was found between the light‐distortion index and CDVA. Conclusions : The multifocal IOLs provided excellent UDVA and functional UNVA despite increased light‐distortion indices. The light‐distortion analyzer reliably quantified a subjective component of vision distinct from visual acuity; it may become a useful adjunct in the evaluation of visual quality obtained with multifocal IOLs. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.